Risk of HIV/STIs among Muslim army conscripts in the three deep southern provinces of Thailand - Awirut Singkun; Kraiwuth Kallawicha; Khemika Yamarat (Tabriz University of Medical Sciences, 2021)
Background: The prevalence of sexually transmitted diseases is an important public health problem, especially in people who are sexually active, such as the army conscript group. However, their knowledge, attitudes, and practices may be influenced by certain cultures and beliefs. This study explored the factors associated with the risk of human immunodeficiency virus (HIV)/sexually transmitted infections (STIs) among the Muslim army conscript in three deep southern provinces of Thailand. Methods: The cross-sectional study design was conducted among 360 Muslim army conscripts. A researcher made questionnaire on knowledge of HIV/STI transmission, attitude toward condom use, and sexual behavior was distributed to the participants in a camp base. The association between the potential predictor variables and the risk of HIV/STI was analyzed using the multiple logistic regression. Statistically significant of the association considered a P value ≤ 0.05. Results: The results suggest that most Muslim army conscripts had a poor knowledge level of HIV/STI transmission (78.7%) and that their attitude toward condom use was at a moderate level (60.0%). The predicted factors were marital status [aOR=0.078, 95% CI=0.035-0.172], substance use before having sex [aOR=8.044, 95% CI=1.288-50.230], stimulant use before having sex [aOR=3.632, 95% CI=1.080-12.211], vaginal sexual intercourse [aOR=26.228, 95% CI=8.370-82.189], and oral sexual intercourse [aOR=2.256, 95% CI=1.106-4.601]. Conclusion: A proper sexual health education program should be developed and delivered to enhance knowledge on HIV/STI transmission among Muslim army conscripts.